FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI KOTA BUKITTINGGI - Afriyanti, Detty (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
The reason for the high number of maternal mortality rates in the city of Bukittinggi is anemia in pregnancy. Mandiangin Health Center is ranked the second highest incidence of anemia which is as many as 29 Pregnant Women. The purpose of this study is the risk factors associated with the incidence of anemia in pregnant women in the city of Bukittinggi. The research design used was descriptive analytic with cross sectional approach. The population is the total number of Pregnant Women who live in the working area of the Mandiangin Health Center as many as 56 people with a total sampling technique, which was conducted in March to May 2019. Based on the results of the study, obtained a significant relationship between the incidence of anemia with economic status (p = 0.033), education (p = 0.025), employment (p = 0.048), age (p = 0,000), parity (p = 0,000), and nutritional status (p = 0.001)